2014
DOI: 10.3389/fphys.2014.00430
|View full text |Cite
|
Sign up to set email alerts
|

The expanded amelogenin polyproline region preferentially binds to apatite versus carbonate and promotes apatite crystal elongation

Abstract: The transition from invertebrate calcium carbonate-based calcite and aragonite exo- and endoskeletons to the calcium phosphate-based vertebrate backbones and jaws composed of microscopic hydroxyapatite crystals is one of the great revolutions in the evolution of terrestrial organisms. To identify potential factors that might have played a role in such a transition, three key domains of the vertebrate tooth enamel protein amelogenin were probed for calcium mineral/protein interactions and their ability to promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…For the design of the SM50 repeat peptide, a 26 amino acid stretch between amino acids 227 and 252 containing four successive polyproline repeat motifs was selected (Gopinathan et al, 2014). SM50 227–252 was chosen as a representative polyproline type II repeat peptide because each of the four repeat motifs contained an N-terminal proline and a C-terminal glutamine, and repeat motif length alternated between six and seven amino acids.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the design of the SM50 repeat peptide, a 26 amino acid stretch between amino acids 227 and 252 containing four successive polyproline repeat motifs was selected (Gopinathan et al, 2014). SM50 227–252 was chosen as a representative polyproline type II repeat peptide because each of the four repeat motifs contained an N-terminal proline and a C-terminal glutamine, and repeat motif length alternated between six and seven amino acids.…”
Section: Methodsmentioning
confidence: 99%
“…While in vertebrates, cells secrete an extracellular matrix to shape the size and properties of the future tooth, mineral nucleation in echinoderms occurs within vacuoles inside of the odontoblastic syncytium, and mineral is deposited once syncytial vacuoles have come into contact with the growing tooth surface (Märkel, 1969; Kniprath, 1974, Märkel et al 1977). A common element among vertebrate and invertebrate teeth is the use of unique biomineralization proteins that facilitate the assembly of biological mineral platelets into complex odontogenic minerals (Gopinathan et al 2014). In the present study we have focused on the biomineralization process in echinoderm teeth and especially on role of polyproline repeat proteins such as SM50 in sea urchin tooth mineralization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent in silico work we found that the major biomineralization proteins can be characterized by a high percentage of disordered residues, including dentin sialophosphoprotein (96%), dentin matrix protein 1 (96%), bone sialoprotein (85%), osteopontin (92%), amelogenin (67%), ameloblastin (82%), and enamelin (92%) [14]. The tooth enamel protein amelogenin is a typical intrinsically disordered biomineralization protein as it controls the growth of apatite crystals for tooth enamel formation [15,16].…”
Section: Significance Of Intrinsically Disordered Proteins Involved Imentioning
confidence: 99%